Vorapaxar, an oral PAR‐1 receptor antagonist, does not affect the pharmacokinetics of rosiglitazone. Issue 1 (28th September 2014) - Kosoglou, Teddy; Kumar, Bharath; Statkevich, Paul; Schiller, James E.; Kantesaria, Bhavna; Hanson, Mary E.; Sisk, Christine McCrary; Cutler, David L.
Abstract Purpose To evaluate the potential effects of vorapaxar on the pharmacokinetics and safety of rosiglitazone. Methods This was an open‐label, two‐period, two‐treatment, fixed‐sequence study in 18 healthy subjects. On Day 1, Period 1, subjects received a single dose of rosiglitazone 8 mg. In Period 2, subjects received vorapaxar 40 mg on Day 1, vorapaxar 7.5 mg once‐daily on Days 2–7, and a single dose of rosiglitazone 8 mg on Day 7. Rosiglitazone and N‐desmethylrosiglitazone pharmacokinetics were assessed alone (Period 1) and after coadministration with vorapaxar (Period 2). Vorapaxar and its M20 metabolite pharmacokinetics were assessed on Day 7, Period 2. Safety and tolerability were assessed throughout the study. Results Coadministration of rosiglitazone with vorapaxar had no effect on rosiglitazone or N‐desmethylrosiglitazone pharmacokinetics. The ratio of geometric means (GMR) and 90% confidence intervals (CI) of the coadministration versus monotherapy for Cmax (GMR 95; 90% CI 88, 103) and AUC0–24 h (GMR 103; 90% CI 98, 108) were within the 80–125% bioequivalence criteria. The metabolite‐to‐parent exposure ratio with and without vorapaxar was unaltered. Coadministration of vorapaxar with rosiglitazone was generally well tolerated. Conclusion Coadministration of vorapaxar with rosiglitazone or drugs metabolized via CYP2C8 is unlikely to cause a significant pharmacokinetic interaction.